Estimativa da demanda evapotranspirométrica do município de Itabaiana-SE - Melo, Almir Querino de (2014)
Agricultural development has required new strategies for efficient production aimed the conservation of all available water resources, which sustainable benefits on farms. In this context, it is important to evaluate and adapt each one of the factors that make up the system of production, including the efficiency and the management of irrigation water. This work had as main objective estimate the demand evapotranspirometric (evapotranspiration of reference - ETo) from climate variables recorded at automatic weather station installed in the city of Itabaiana-SE. It was observed that the minimum value of demand evapotranspirometric was 1,2mm and the maximum value was 6.6mm. It has been proven that the sensors and the communication system of stations installed in Itabaiana are functioning properly, within the specifications of the manufacturers.